Glutamine for prevention and alleviation of radiation‐induced oral mucositis in patients with head and neck squamous cell cancer: Systematic review and meta‐analysis of controlled trials. Issue 10 (9th July 2021) - Alsubaie, Hemail M.; Alsini, Albaraa Y.; Alsubaie, Khaled M.; Abu‐Zaid, Ahmed; Alzahrani, Faisal R.; Sayed, Suhail; Pathak, Alok K.; Alqahtani, Khaled H.
Abstract: We conducted a systematic review and meta‐analysis of randomized controlled trials (RCTs) that investigated glutamine efficacy in preventing and alleviating radiation‐induced oral mucositis (OM) among patients with head and neck (H&N) cancer. We screened five databases from inception till February 4, 2021 and followed the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses (PRISMA) guidelines. We included 11 RCTs, comprising 922 patients (458 and 464 patients were assigned to glutamine and control group, respectively). The incidence and onset of radiation‐induced OM of any grade did not substantially differ between both groups. However, glutamine substantially reduced the severity of radiation‐induced OM, as reflected by the reduced incidence of severe OM and reduced mean maximal OM grade score. Additionally, glutamine significantly decreased the rates of analgesic opioid use, nasogastric tube feeding, and therapy interruptions. Oral glutamine supplementation demonstrated various therapeutic benefits in preventing and ameliorating radiation‐induced OM among patients with H&N cancer.